Study of Temperature Change in Iraq Between 2000-2020 and Its Effects on Rainfall Levels and Agriculture - Bashayir Jasem Mohammed (Academia Open, 2024)
This study is based on the understanding of the impact of temperature change on the percentage of rainfall in selected areas of Iraq, the data of Iraqi government institutions were relied upon in conducting the statistical assessment on the rates shown by the annual reports of rainfall rates in a number of Iraqi governorates from Mosul in the north to Basra in the south, the period 2000-2020 was chosen, and the CORDEX downsizing project was used, by developing scenario number RCP8.5, it has been shown by using the necessary calculations that rainfall levels will decrease at significant rates in the future if the temperature rises in the same pattern as the current one, which predicts an uncertain future for the nature of the climate in Iraq, this will have a serious impact on the agriculture, industry and all other sectors, this requires the Iraqi government to provide strategic solutions for the coming period. Highlights : Government Data Assessment: Reliance on Iraqi government institutions' data for statistical assessment. Future Projections: Use of the CORDEX downsizing project to develop scenario RCP8.5. Critical Implications: Calculations reveal significant future decreases in rainfall, posing serious threats to agriculture, industry, and other sectors in Iraq. Keywords : Temperature Change, Rainfall Levels, Iraq, CORDEX Downsizing, RCP8.5.